Clinical and Prognostic Features of Patients With Esophageal Cancer and Multiple Primary Cancers: A Retrospective Single-institution Study. Issue 3 (March 2018) - Baba, Yoshifumi; Yoshida, Naoya; Kinoshita, Koichi; Iwatsuki, Masaaki; Yamashita, Yo-ichi; Chikamoto, Akira; Watanabe, Masayuki; Baba, Hideo
Abstract : Objective: To investigate the clinical and prognostic characteristics of patients with esophageal cancer and multiple primary cancers. Summary Background Data: Patients with esophageal cancer frequently have multiple primary cancers, the presence of which may complicate physicians' decision-making because the clinical and prognostic features of such patients remain unknown. Methods: This retrospective single-institution study included 538 consecutive patients who had undergone resection of esophageal cancer. The Cox proportional hazard model was used to compute the hazard ratio (HR) for mortality. Results: At the time of surgery, 163 patients (30%) had multiple primary cancers (77, metachronous; 86, synchronous). Multiple primary cancers were significantly associated with alcohol use and tobacco smoking (Brinkman index). Patients with synchronous cancers had significantly shorter overall survival than those without multiple primary cancers (log-rank P = 0.032; univariate HR = 1.53, 95% confidence interval 1.02–2.17, P = 0.040; multivariate HR: 1.61; 95% confidence interval: 1.08–2.36; P = 0.020). Patients with metachronous cancers had similar prognoses to those without multiple primary cancers. The prognostic effect of synchronous cancers on overall survival was particularly prominent in patients with Stage I esophageal cancer (log-rank P = 0.0002). Conclusions: Multiple primary cancers are associated with a history of tobacco and alcohol use, supporting the concept of field cancerization. Synchronous multiple primary cancers may be an independent predictor of poorer long-term survival in patients undergoing resection of esophageal cancers. Abstract : Supplemental Digital Content is available in the text